Peranan Kepolisian Lalu Lintas Dalam Penegakan Hukum Terhadap Pelanggaran Lalu Lintas Yang Dilakukan Pengendara Sepeda Motor Di Wilayah Hukum Sektor Tampan - Maxtry Parante; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Motorcycle used from the lower class to upper class. Lack of supervision of the police is one of the factors which caused the number of traffic offenses committed particularly motorcycle riders. Motorists assume that the regulations be implemented if the police are overseen. The purpose of this paper is the first, the role of Traffic Police Sector Handsome in law enforcement against traffic offenses committed motorcyclists in the jurisdiction of Sector Handsome, both barriers experienced by the Traffic Police Sector Handsome in law enforcement against traffic offenses committed motorcyclists in the jurisdiction of Sector Handsome, the third attempt by the Traffic Police Sector Handsome in overcoming the obstacles that arise in dealing with law enforcement on traffic offenses committed motorcyclists in the jurisdiction of Sector Handsome.This type of research dogolongkan in this type of sociological research, ie research on the effectiveness of the law being in force, the nature of this research is descriptive research that systematically describe, facts and characteristics of the object under study accurately. Penellitian was conducted in the jurisdiction of Sector Handsome, while the overall population and sample the parties relating to the issues examined in this study. Source of data used primary data and secondary data consists of primary legal materials, secondary and tertiary. Data collection techniques in this study with a questionnaire, observation, interview and literature study. Analysis of the data used is based on the description line qualitative and draw conclusions deductively that from the general to the particular.From the research problem, there are three main things that can be inferred. First, the role of the traffic police in the enforcement of the traffic violations committed motorcyclists in the jurisdiction of Sector Handsome done with pre-entif, preventive and repressive. Second, barriers experienced by the Traffic Police Sector Handsome in enforcement of the traffic violations committed motorcyclists in the jurisdiction of Sector Handsome comes from internal factors and external factors. Third, the efforts made by the Traffic Police Sector Handsome in overcoming the obstacles that arise in dealing with law enforcement on traffic offenses committed motorcyclists in the jurisdiction of Sector Handsome convening dissemination to the public, especially motorcycle riders in terms of order traffic. The first author's suggestion, the police force should improve its performance. Second, add a unit of traffic police personnel. Third, the traffic police working together with the community to make socialization or counseling.Keywords: Role-Police-Bike-riders motor- Traffic